„Emmanuelis Alvari syntaxis” – przez dwa wieki - Popiak, Wanda (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The paper briefy touches the Latin syntax elaborated by Emmanuel Alvares (1526–1582). The book was published in Poland in 1577 and was used in our schools till 1815. The author of the paper shows how the manual was employed in Poland with the passing of time.
Emmanuelis Alvari Syntaxis during two centuries
Keywords: Latin syntax; Emmanuel Alvaris